FOTO BENCANA ASAP DI PROVINSI RIAU PADA INSTAGRAM @INFOPKU_ (ANALISIS SEMIOTIKA ROLAND BARTHES) - Endah Rizqi Pratiwi; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Instagram @infopku_ is one of social media account which often sharing information about Pekanbaru or Riau, including information about forest fire in 2016 and make Indonesia increasingly synonymous with smoke disaster. Instagram @infopku_ share it through photos along with caption which was uploaded. Photo is one of the nonverbal communication media, it is important to examine the meaning of it. In this research, the writer wanted to see the message of @infopku_ photos.The method used qualitatively with Roland Barthes semiotic analysis which is part of the data analysis method in representative qualitative research. The data used was taken from Instagram and some references from internet. After collecting the data, it was analyzed to get the results.The findings of denotation meaning research showed events were happening directly.The connotation meaning explained that forest preservation is human responsibility.The mytical meaning of the five photographs generally contained of facts about the phenomenon that happened could be a warning to be more vigilant in dealing with it. Through the five photos was delivered to the whole Riau society especially to care about the condition of the forest whch is rich of benefits.